Demand and Satisfaction with Rehabilitation Knowledge and Services in Community Residents - Beibei LI; Yuehong BAI; Jian YANG; Jianping ZHANG; Guizhen LIU; Yiming XU (康复学报, 2019)
Objective:To investigate the prevention knowledge of cervical spondylosis, lubar intervertebral disc protrusion, knee osteoarthritis and stroke, and their satisfaction and demand for community rehabilitation services in Shanghai residents, in order to popularize rehabilitation knowledge and improve rehabilitation treatment services in later stage, and to provide baseline data for establishing a complete three-level rehabilitation network and provide high-quality community rehabilitation services.Methods:The permanent residents in six street community health service centers and a level II hospital in Xuhui district (including Changqiao street, Caohejing street, Tianlin street, Tianping street, Xietu street, Xujiahui street and Dahua hospital) were chosed as the experimental group and subjects of the late intervention, and the residents in Putuo district (including Changfeng street, Caoyang street and other streets) as the control group. The time limit for investigation was from November 2013 to February 2014. Residents in Xuhui and Putuo district were investigated with questionnaire of their awareness of prevention knowledge of cervical spondylosis, lubar intervertebral disc protrusion, knee osteoarthritis and stroke, and satisfaction degree of community rehabilitation services by random cluster sampling, then their demands were analyzed.Results:We provided 4 000 questionnaires in Xuhui district, 3 461 were effective of the 3 565 recovered ones, the efficient rate was 97.08%. Correspondingly, we provided 1 000 questionnaires in Putuo district, 792 were effective of the 810 recovered ones, the efficient rate was 97.78%. The residents'awareness degrees of basic knowledge about cervical spondylosis, lubar intervertebral disc protrusion and knee osteoarthritis in two districts were 79.55%-95.05%, but the awareness degrees was deficient about stroke, especially in Putuo district, the awareness degrees was only 43.06%. The satisfaction degree of residents in Xuhui district on the rehabilitation equipment was 90.86%, the doctors'diagnosis and treatment was 80.33%, the technician skill was 83.17%, and the comprehensive rehabilitation services was 79.44%. The satisfaction degree of residents in Putuo district on the rehabilitation equipment was 60.21%, the doctors'diagnosis and treatment was 59.47%, the technician skill was 63.30%, and the comprehensive rehabilitation services was 63.29%.Conclusion:The understanding of cerebrovascular diseases, and regular education should be strengthened, residents in Shanghai are lack in participation to the community rehabilitation, and the coverage of rehabilitation treatment need to be improved. The facilities, medical teams and the services of community rehabilitation in Shanghai should be strengthened. More favorable policy should be issued to develop the community rehabilitation in Shanghai to meet the needs of the residents.